UNDERSTANDING BODY IMAGE AND ITS PSYCHOLOGICAL CONSEQUENCES - Kumar Ujwal (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The focus of present research is on understanding body image and its psychological consequences. We formulated four objectives in our study a) to examine the body image dissatisfaction in different age groups b) to examine the relationship between body image dissatisfaction, self-esteem and aggression c) to see the difference between dysmorphic and non-dysmorphic on body image dissatisfaction, self-esteem and aggression d) to examine whether the body dissatisfaction is more in males or females. Data has been collected from total 60 participants which included 20 participants of people of age group 20 to 35, 20 participants of people of age group 45 to 60 and 20 participants of people of age group 65 above. The total 60 participants also involve 30 males and 30 females because we also want to know the gender difference in relation to body image. The results showed more body dissatisfaction is more in early adulthood as compared to middle and late adulthood. The result also showed that no significant difference exists between body image dissatisfaction and aggression. The result showed that there is significant difference between dysmorphic and non-dysmorphic on body image dissatisfaction, self-esteem and aggression. The result also showed on the basis of mean difference that body dissatisfaction is more in males as compared to females but there is no significant difference.